Pectin encapsulated novel nanocomposite augments wound healing in Sprague Dawley rats - Kunal Kishore; Saranga Rajesh; Sneha Sivadas; N. Selvasudha; R. Barathidasan; Hannah R. Vasanthi (Carbohydrate Polymer Technologies and Applications, 2023)
The complexity of the tissue remodeling process makes the treatment options for wound healing inadequate. Herein, the potential wound-healing activity of a novel nanocomposite with pectin and keratin incorporating silver nanoparticles and ferulic acid has been evaluated. Silver concentration, secondary structural stability of keratin, and the presence of ferulic acid and nano silver as a complex molecule within the nanocomposite were confirmed by XPS, CD spectroscopy, and ESI-MS analysis, respectively. The effects of the nanocomposite (NC) on cell migration and the role of apoptosis in wound healing were studied by scratch assay and (A.O./EtBr) staining, respectively. Subsequently, in vivo studies were carried out in male Sprague Dawley rats. Wound tracings measured exhibited significant wound contraction. Further, the relative gene expression of wound–healing biomarkers MMP2, MMP8, and KGF increased considerably in the 75 mg test group compared to the negative control group indicating a faster epithelialization phase of wound healing. Histopathological observations revealed remarkable skin regeneration in the test group. Altogether, the nanocomposite at 75 mg dose exhibits enhanced cell migration capability, reepithelialization and tissue remodeling activity than the standard, possibly due to the synergistic influence of the natural biomolecules. Therefore it is concluded that the NC exhibits accelerated wound healing with negligible toxicity.